EVALUASI RESIKO APLIKASI IKAN TRANSGENIK DALAM KEGIATAN BUDIDAYA - BOBY DANI DARMAWAN (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2013)
There are many problematic issues challenging the success of fish farming. In particular, the very intensive, monocultural nature of fish farming raises some fundamental questions about the sustainability of this type of farming. Using genetically modified organisms (GMO) for fish cultivation is one of those to help the farmer to increase the production. By focusing on